Demand Management at Households in Sri Lanka through Dynamic Pricing and Demand Information Systems - Alfered Canistus, G.; Sakthivelnathan, N.; Thiruparan, N.; Jayasinghe, D.H.G.A.E. (SLEMA Journal, Volume 24 No.1, 2021)
In electrical power systems, expensive peaking power plants need to be operated to serve the peak demand. In Sri Lanka, the peak usually occurs late in the evening, caused by household demand. Peaking power plants are expensive to operate, compared with baseload power plants. Therefore, any electric utility desires to reduce the peak demand using demand management techniques. Demand management efforts in Sri Lanka are limited to mandatory time of use pricing for medium and large institutional customers. Household customers, the dominant customer category in terms of electricity sales, require to be brought into the time of use pricing regime. The main objective of this research was to conduct case studies to examine whether household customers are sensitive to price incentives. Financial incentives and information about their electricity demand were provided to a selected number of household customers to encourage them to reduce electricity use in the peak period. It was found that the approach has caused a reduction of the peak-time demand in all the selected households. This demand management technique may be refined and expanded to achieve a significant change in the load curve. The paper provides the mathematical formulation of a potential approach to dynamic pricing. The utility CEB may further analyses and implement this demand management approach.
Keywords: Dynamic pricing; Peaking power plant